The effect of Blended Learning on Performing Some Ball Skills in Rhythmic Gymnastics - Hasoon, Elham Ali; Mutar, Shaima Abed (Journal of Physical Education, 2021)
The research aimed at designing an electronic program blende with scientific classes as well as identifying its effect on learning some ball skills in rhythmic gymnastics. The researchers used the experimental method on (20) female students divided equally to controlling and experimental groups, they also designed an electronic program blended with class learning for some ball skills in rhythmic gymnastics. The results showed that the experimental group surpassed in using blended learning (Electronic – class) compared to the controlling group. The researchers concluded that all forms of information delivery between learner and teacher are means for changing motor behavior that differs from one learner to the other depending on the teaching style and its effect on the learner. In addition to that, the relation between learning motor skills and teaching technology increases in complicated skills.